Vaginulid Slugs in Central America, with Emphasis on the Bean Slug - Rueda, Alfredo; Caballero, Rafael; Kaminsky, Reina; Andrews, Keith L. (Escuela Agricola Panamericana, 2014, 2014)
The .family Vaginulidae (=Veronicellidae) (Mollusca: Soleolifera) has a pantropical to subtropical distribution. Of the known ca. 100 species in this family, more than half occur in the Americas. Vaginulíd slugs are important in Central America for two reasons. First, they are pests in several staple food and horticultura! crops. Second, vaginulid slugs are intermediate hosts of the nematode Angiostrongylus costaricensis (Morera and Cespedes) that parasitizes humans. Costs associated wíth the disease were estímated to be US$5 million annually (Andrews, 1987a).